Β‐blockers and ACE inhibitors are not a risk factor for severe systemic sting reactions and adverse events during venom immunotherapy. Issue 7 (11th March 2021) - Sturm, Gunter Johannes; Herzog, Sereina Annik; Aberer, Werner; Alfaya Arias, Teresa; Antolín‐Amérigo, Darío; Bonadonna, Patrizia; Boni, Elisa; Bożek, Andrzej; Chełmińska, Marta; Ernst, Barbara; Frelih, Nina; Gawlik, Radoslaw; et al.
Abstract: Background: There is controversy whether taking β‐blockers or ACE inhibitors (ACEI) is a risk factor for more severe systemic insect sting reactions (SSR) and whether it increases the number or severity of adverse events (AE) during venom immunotherapy (VIT). Methods: In this open, prospective, observational, multicenter trial, we recruited patients with a history of a SSR and indication for VIT. The primary objective of this study was to evaluate whether patients taking β‐blockers or ACEI show more systemic AE during VIT compared to patients without such treatment. Results: In total, 1, 425 patients were enrolled and VIT was performed in 1, 342 patients. Of all patients included, 388 (27.2%) took antihypertensive (AHT) drugs (10.4% took β‐blockers, 11.9% ACEI, 5.0% β‐blockers and ACEI). Only 5.6% of patients under AHT treatment experienced systemic AE during VIT as compared with 7.4% of patients without these drugs (OR: 0.74, 95% CI: 0.43–1.22, p = 0.25). The severity of the initial sting reaction was not affected by the intake of β‐blockers or ACEI (OR: 1.14, 95% CI: 0.89–1.46, p = 0.29). In total, 210 (17.7%) patients were re‐stung during VIT and 191 (91.0%) tolerated the sting without systemic symptoms. Of the 19 patients with VIT treatment failure, 4 took β‐blockers, none an ACEI. Conclusions: This trial provides robust evidence that taking β‐blockers or ACEI does neither increase the frequency of systemic AE during VIT nor aggravate SSR. Moreover, results suggest that these drugs do not impair effectiveness of VIT. (Funded by Medical University of Graz, Austria; Clinicaltrials.gov number, NCT04269629). Abstract : Patients under antihypertensive treatment with β‐blockers and angiotensin‐converting enzyme inhibitor (ACEI) do not have a higher risk for severe insect sting reactions. The intake of β‐blockers and ACEI does not increase the frequency of systemic adverse events during venom immunotherapy (VIT). Results suggest that β‐blockers and ACEI do not impair VIT effectiveness. Abbreviations: ACEI, angiotensin‐converting enzyme inhibitor; VIT, venom immunotherapy.